Assessment of the Inhibitory Potential of Flavonoids on the Internalin A Protein of Listeria monocytogenes Through Molecular Docking - Sillagana Verdezoto, Cristian (Orbital: The Electronic Journal of Chemistry, 2025)
Listeria monocytogenes is an intracellular pathogen capable of colonizing its hosts through virulence factors, with the Internalin A (InlA) protein being particularly notable. This study evaluated the binding affinity and interactions of 20 flavonoids through molecular docking, aiming to identify potential inhibitors of InlA. The flavonoids, selected for compliance with Lipinski’s rule, were analyzed using AutoDock Vina and visualized in Chimera, PyMOL, and LigPlot+. Biological activity and pharmacokinetic predictions were conducted using PASS, ADMETlab, SwissADME, and ProTox-II, showing that the selected flavonoids have potential as antioxidant agents and membrane stabilizers. The results identified silibinin and puerarin as the compounds with the highest binding affinity (-11.93 and -10.94 kcal/mol, respectively), in addition to demonstrating potential as antioxidants and membrane stabilizers, with low toxicity. This study suggests that the selected flavonoids may inhibit the virulence of L. monocytogenes; however, further experimental and in vivo validation is required to confirm their inhibitory effect on InlA.